Busby Berkeley, broken rhythms and dance direction on the stage and screen. Issue 1 (1st March 2013) - Robbins, Allison
On the 1920s revue stage, dance director Busby Berkeley created 'broken' chorus numbers in which dancers performed rhythms that contradicted the metrical structure of the musical arrangement. This musico-choreographic aesthetic was influential in the filming and editing of Berkeley's subsequent Hollywood musical numbers. I demonstrate how his numbers in Whoopee! (1930) retain characteristics from his stage routines and examine how those elements shaped the way he filmed and edited tap choreography in the distinctly cinematic numbers from 42nd Street (1933) and Gold Diggers of 1935 (1935). Berkeley's cinematography is notable not just for its innovative camera angles but for continuity editing initiated by movement and music.